Penentuan Wilayah Terdampak Covid-19 dengan Menggunakan Metode Analytical Hierarchy Process, Simple Additive Weighting dan Weighted Product - Supriyadi, Mohamad Didit; Andryana, Septi; Gunaryati, Aris (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2021)
Corona virus (Covid-19) is a new virus that has spread to many countries in the world, including Indonesia in 2020. This virus has spread to all provinces in Indonesia. The 3 provinces with the highest number of cases are DKI Jakarta, East Java and Java West. Currently, the ranking of areas affected by Covid-19 is only done based on the confirmed number of each province. Therefore, this study aims to rank the affected areas of Covid-19 using the Analytical Hierarchy Process, Simple Additive Weighting and Weighted Product methods. The combination is done based on the advantages of each method. The AHP method is used to analyze the criteria to produce criteria with good consistency, then the ranking process of each alternative is carried out using the SAW and WP methods. This research is expected to provide recommendations for the affected areas to make various efforts to reduce the confirmed figures.Keywords:Analytical Hierarchy Process; Decision Support System; Simple Additive Weighting; Weighted Product.